1981
DOI: 10.1136/bmj.283.6295.819
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of pyogenic liver abscess.

Abstract: Sixteen patients with pyogenic liver abscesses were studied over 10 years to discover the causative organisms of the condition. Pus was subjected to Gram-negative smear or gas-liquid chromatography to detect volatile acids characteristic of anaerobes and then cultured. All isolates were identified by conventional methods and tested for sensitivity to appropriate antimicrobial agents. Bacteria were grown from the liver abscesses in all 16 patients. Streptococcus milleri Lancefield group F was the commonest orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
2

Year Published

1983
1983
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(29 citation statements)
references
References 19 publications
1
26
0
2
Order By: Relevance
“…In these cases PLA, the predominant organism were E. Coli 5(50%) and other organism Proteus 3(30%) Pseudomonas and Klebsiella each 1(10%). These studies are in agreement with Moore et al (1993) in U.K, McDonald (1984) 3 in Australia, Sherlock et al (1993) in U.K, they found E. Coli as the Commonest organism [22][23][24] . In contrast Yeah et.al (1997) in Singapore, reported Klebsiella Pneumoniae as the commonest organism in PLA 25 .…”
Section: Discussionsupporting
confidence: 82%
“…In these cases PLA, the predominant organism were E. Coli 5(50%) and other organism Proteus 3(30%) Pseudomonas and Klebsiella each 1(10%). These studies are in agreement with Moore et al (1993) in U.K, McDonald (1984) 3 in Australia, Sherlock et al (1993) in U.K, they found E. Coli as the Commonest organism [22][23][24] . In contrast Yeah et.al (1997) in Singapore, reported Klebsiella Pneumoniae as the commonest organism in PLA 25 .…”
Section: Discussionsupporting
confidence: 82%
“…"S. milleri" has been implicated in other reports as a cause of brain abscess (51) and meningitis (39,72). "S. milleri" also functions as a pathogen in pyogenic liver abscess (9,40,54,59) and appendicitis (49,61). Mannitol-fermenting "S. milleri," frequently isolated from the female genital tract, has been implicated in two cases of neonatal sepsis (16).…”
Section: Clinical Significance Of "S Milleri"mentioning
confidence: 99%
“…Although often isolated in pure culture, "S. milleri" can be found in polymicrobial infections (44,54,68,76,79). This raises the possibility of synergistic infections involving S. milleri, but this phenomenon has yet to be investigated.…”
Section: Clinical Significance Of "S Milleri"mentioning
confidence: 99%
“…In a recent population-based epidemiological study it was observed that members of the SMG were responsible for as many invasive streptococcal diseases as all other streptococci combined (25). The members of the SMG are also the most common cause of brain (10,13) and liver (12,28) abscesses. Furthermore, members of the SMG are recognized respiratory pathogens.…”
mentioning
confidence: 99%